Digitalization of Banking - Issues and Challenges - SHARMA, NIKET (The journal of contemporary issues in business and government, 2021)
The bleeding edge world where everyone is existing is administered through the thought called "Digitalization". The organization of India starting late declared Digital India Programmed through a fantasy to change India into a deliberately authorized culture and data reduced. In all divisions of the economy and banking sector the prospect of digitization has acknowledged huge jobs, which are no exclusion. For Indian banking, digitalization has become unequivocal, which expect critical occupation in helping budgetary consolidation and which is transcendently stressed over outfitting better organizations to customers close by an opportunity to procure in not all that inaccessible future. Indian monetary fragment is achieving colossal advancement starting late, consoling higher proportion of capital plan, which is an immediate consequence of digitalization of banking. No matter how Indian money is digitalized, numerous problems and challenges, in particular in natural banking, are to be tackled. This research paper is intended to examine and widen the perspective of the challenges and problems in the field of rural banking digitalization.